PEMAHAMAN HADIS-HADIS MISOGINIS MENURUT ULAMA HADIS DAN FEMINIS MUSLIM INDONESIA - Usamah, Usamah (Faculty of Ushuluddin and Humanities, 2013)
This article analyses some prophetic sayings (hadith) considered misogenic, by comparing commentaries of the medieval ulama and the contemporary Muslim feminists in Indonesia. The first hadith is about woman leadership. Based on this hadith, many traditional ulama do not allow woman to be the leader. However, some medieval ulama such as Jalaluddin al-Sayuthi, al-Tabari and Abu Hanifah, do allow woman to become a leader. In line with this view, Indonesian Muslim feminists argue that woman deserves to be a leader like man, and the hadith should be understood in its specific context, namely that it talks about Persian Imperium which was led by a woman, so that it cannot be generalized. Morever, the hadith is ahad, reported by one line of transmitters. The second hadith is about Godâs condemnation on a wife who refuses her husband for sexual intercourse. The traditional medieval ulama and Indonesian Muslim feminists agree that this hadith is also applied to man, that is, if he refuses his wife. Finally, the hadith stating that woman is less intelligent, according to the traditional ulama, means not to humiliate her, but to be aware of her temptation.